MILD OBESITY IS PROTECTIVE AFTER SEVERE BURN INJURY - Jeschke, Marc G. (2013)
OBJECTIVE: To assess the impact of obesity on morbidity and mortality in severely burned patients. BACKGROUND: Despite the increasing number of people with obesity, little is known about the impact of obesity on postburn outcomes. METHODS: A total of 405 patients were prospectively enrolled as part of the multicenter trial Inflammation and the Host Response to Injury Glue Grant with the following inclusion criteria: 0 to 89 years of age, admitted within 96 hours after injury, and more than 20% total body surface area burn requiring at least 1 surgical intervention. Body mass index was used in adult patients to stratify according to World Health Organization definitions: less than 18.5 (underweight), 18.5 to 29.9 (normal weight), 30 to 34.9 (obese I), 35 to 39.9 (obese II), and body mass index more than 40 (obese III). Pediatric patients (2 to ≤18 years of age) were stratified by using the Centers for Disease Control and Prevention and World Health Organization body mass index-for-age growth charts to obtain a percentile ranking and then grouped as underweight (<5th percentile), normal weight (5th percentile to <95th percentile), and obese (≥95th percentile). The primary outcome was mortality and secondary outcomes were clinical markers of patient recovery, for example, multiorgan function, infections, sepsis, and length of stay. RESULTS: A total of 273 patients had normal weight, 116 were obese, and 16 were underweight; underweight patients were excluded from the analyses because of insufficient patient numbers. There were no differences in primary and secondary outcomes when normal weight patients were compared with obese patients. Further stratification in pediatric and adult patients showed similar results. However, when adult patients were stratified in obesity categories, log-rank analysis showed improved survival in the obese I group and higher mortality in the obese III group compared with obese I group (P < 0.05). CONCLUSIONS: Overall, obesity was not associated with increased morbidity and mortality. Subgroup analysis revealed that patients with mild obesity have the best survival, whereas morbidly obese patients have the highest mortality.